Striped bass and other Morone culture - Harrell, Reginal M. (Developments in aquaculture and fisheries science, 1997)
This book is an up-to-date discussion of the culture of striped bass and other Morone spp. The subject matter is broken down into functional components of the spawning, husbandry, and economics of the industry, and is written by some of the leading scientists in each of the respective areas of discussion. The chapters on reproduction, nutrition, environmental requirements, transportation, economics and fish processing are not found anywhere else in the striped bass literature. The chapter on water quality takes a very non-traditional approach to considering the impact water quality has on the production success of Morone and offers some very thought-provoking ideas on water management. Primarily written as a reference work, this book is intended to complement existing technique manuals.